Sodium benzoate treatment decreased amyloid beta peptides and improved cognitive function among patients with Alzheimer’s disease: secondary analysis of a randomized clinical trial - Chieh-Hsin Lin; Hsien-Yuan Lane (Translational Psychiatry)
Abstract With the recent approval of anti-amyloid beta (Aβ) monoclonal antibody infusion therapies for Alzheimer’s disease (AD), more feasible and safter Aβ-reducing approaches are anticipated. Previous studies showed that 750-mg/day or 1000-mg/day (but not 500-mg/day) sodium benzoate treatment improved cognitive function in AD patients with excellent safety and that benzoate decreased Aβ burden in an animal AD model. The current study aimed to explore whether oral sodium benzoate was able to reduce Aβ peptides in AD patients and whether Aβ before treatment was correlated with cognitive improvement after treatment. This secondary analysis used data from a double-blind trial, in which 149 patients with mild AD were randomized to receive oral placebo or one of three benzoate doses (500, 750, or 1000 mg/day). Cognitive function and plasma Aβ 1–40 and Aβ 1–42 levels were measured before and after treatment. When compared to placebo, benzoate therapy at effective doses (750 and 1000 mg/day) reduced Aβ 1–40 and the sum of both Aβ peptides (Aβ 1–40 plus Aβ 1–42) in AD patients. Moreover, higher Aβ 1–42 levels at baseline were associated with better cognitive improvements after benzoate treatment at effective doses in the patients. The findings suggest that sodium benzoate therapy can reduce Aβ 1–40 and the total Aβ in AD patients and higher Aβ 1–42 levels before treatment predict better cognitive improvements. Due to its superior safety and convenient administration, sodium benzoate has the potential to be a novel Aβ-reducing therapy for AD treatment. Trial registration Name of trial registry: NMDA Enhancer for the Treatment of Mild Alzheimer’s Disease. Identifying number: ClinicalTrials.gov Identifier: NCT03752463 ( https://clinicaltrials.gov/ct2/show/NCT03752463 ). Registration date: 2018-11-21.